(3QSGdI aj eYQaI BdGJ jYde HgG CHYGO GdCTjGA GdTGNUI aj GdghGA hGdJi Ydi HSjW GdCQV hGZhGQ GdChOjI hGdBHGQ hYQhV GdCfgGQs - (3GdaVd Hf MGJe GdfjQjRj, CHh GdYHGS,J (B310 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3bGd GdaVd Hf MGJe bGd CQSWGdjS (B: (3Ef GWhd GYeOI GdLHGd hCHYO HYO GdZjhe ai GdLh s
(3CdagG bGSe Hf YHOGddg Hf ehSi s
(3ef cJGH Qbe (B81 (3MSGH (B"(3QSGdI ai EjVGM hLOGf CHYGO eGHjf GdfGXQ(B"s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B147 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B66s
Keywords: (3GdQjGVjGJs